Reconstruction of the Kafaah Concept in Marriage - Suwarjin Suwarjin (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
Kafaah in marriage aims to create a complete and harmonious family. However, the old construction of kafaah contains discriminatory and problematic nuances. This can be seen from the criteria for kafaah, which are all physical-material, except for religion and piety. Humans are polarized into primordial partitions: beautiful-ugly, rich-poor, aristocratic-ordinary people, and free-slave. This polarization gives birth to discriminatory attitudes in society. In fact, Islam came to eliminate discriminatory social barriers. Through the maqâshid al-syâri`ah approach, this research seeks to reconstruct the concept of kafaah in several aspects, namely: reorienting the purpose of applying kafaah, repositioning kafaah rights, reviewing kafaah criteria and classifying kafaah. Maqâshid al-syâri`ah is presented here not as a doctrine to understand a particular context of Islamic law, but as a method to reconstruct the existing concept of kafaah. The goal is to produce a new concept of kafaah that is more substantive and humanist. From the results of the study, several conclusions were found. First, Kafaah legality is ijtihad because there are no valid texts found. Second, The construction of kafaah is influenced by the patrilineal system of Arab society. Third, Reconstruction of the concept of kafaah is carried out in two ways: (1) to include other criteria other than the seven criteria set by classical fiqh. (2) to compare the kafaah criteria between prospective husbands and prospective wives holistically. This things needs to be done to fulfill the current sense of justice and benef of the Muslim family.